Animal products market study: Between scientific rigor and reality - Ancuța Marin; Rodica Chetroiu; Lidia Iurchevici (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 10th Edition, 2019)
Abstract: The paper represents the result of the efforts made to develop a market study within the first subsystem of the marketing - the entries on the market, meaning the production sector, by applying a questionnaire addressed to the producers of cow's milk, sheep meat, pork, broiler. Even though the number of the questionnaires fullfilled (from 69 animal farms) is insufficient for the information contained to be statistically validated as a representative sample, given the data and information received from the producers who were opened to participate in this study and who deserves our appreciation, we felt that they must be known. The results of the opinion poll show that the respondents do not, in general, conclude contracts for the sale of the products, and the valorisation of the production takes place on the local and county market, only the larger farms delivering on the national market. The production sold is generally unprocessed, in a proportion of about 65%. The sources of financing of the activity are own sources in the proportion of 40-60%, loans 30-50%, subsidies 10-65% and access of European funds 10-15%. The questionnaire also reveals the problems that the breeders encounter during the production. Many of them invoke the low selling price of production, the fact that the takeover of the production has an irregular frequency, and the payment is made late.
Keywords: O12; O13; 330; market; milk; meat; producer; questionnaire